APPLICATION OF THE DESIGN AND CONSTRUCTION RESULTS OF AN OBLIQUE LUMBAR RADIOGRAPHY EXAMINATION AID - Agustina Dwi Prastanti; Akhmad Haris Sulistiyadi; Bagus Abimanyu (Poltekkes Kemenkes Semarang, 2025)
Oblique lumbar radiographic examinations require assistive devices to facilitate patient positioning and produce accurate radiographs showing the Scottie dog sign. Oblique lumbar patient positioning requires the patient to be tilted 45 degrees to the right or Right Posterior Oblique (RPO) and 45 degrees to the left or Left Posterior Oblique (LPO). The results of the design and construction of the oblique lumbar radiography examination aid need to be implemented in real-world healthcare services within the hospital's radiology unit. The purpose of this community service is to introduce, educate, and implement the results of the design and construction of an oblique lumbar radiography examination aid. The community service methods are thru lectures, discussions, and hands-on practice. The community service element involves Radiographers in hospitals where there is a demand for oblique lumbar radiographic examinations, as well as student interns. The direct application of the oblique lumbar radiographic examination aid by Radiographers on patients has successfully produced oblique lumbar radiographs that clearly show the Scottie dog sign, thereby improving healthcare services, particularly in the field of radiology.